Prediction of functional outcome in patients with primary intracerebral hemorrhage by clinical-computed tomographic correlations - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; Abdul Rashid, Mohd Amran; Che Abdullah, Shahrin Tarmizi; Mohd Shah, Azarisman Shah (Research Department, Isfahan University of Medical Sciences, 2012)
Background: Primary intracerebral hemorrhage (PICH) remains the deadliest and most disabling form of stroke. The aim of our study was to determine the potential predictors for survival and neurological recovery in PICH patients by clinical-computed tomographic (CT) correlation. Materials and Methods: A prospective study conducted among PICH patients at a tertiary care hospital. The clinical and CT scan findings were correlated with the functional outcome using modified Rankin scores (mRS) of 0-5 at discharge and during six months follow-up. Results: The clinical and CT findings in 160 (93 male and 67 female) eligible adult patients with age range from 25 to 85 years (mean age 58.30 ± 11.44 years) were analyzed. The mean Glasgow Coma Scale [GCS] score was significantly higher among survivors. (12.8 ± 0.4 vs. 8.5 ± 0.5, P < 0.001) Based upon the pattern of the CT findings, the best outcome in terms of survival was for the patients with ICH in basal ganglia/internal capsule region (86.7 %), followed by lobar hemorrhage (67.1%). Good functional outcome was associated with a hematoma volume of less than 30 ml. At discharge majority of the survivors were functionally dependent 76 (70.4%) and only 32 (29.6%) achieved functional independence. The significant independent predictors of in- hospital survival were GCS score > 9 (OR 10.8; 95% CI 4.061 to 28.719), basal ganglia/internal capsule bleed (OR 9.750; 95% CI 2.122 to 45.004), hematoma volume <30 ml (OR 11.476; 95% CI 4. 810 to 27.434), no mid line shift (OR 4.901; 95% CI 2.405 to 9.987) and no intraventricular extension of hemorrhage (OR 7.040; 95% CI 3.358 to 14.458). Conclusion: Outcome and functional status at discharge were well correlated with the initial CT scan findings and GCS score.